RESERVOIR CHARACTERIZATION AND RESEREVES ESTIMATION IN LOWER KEUTAPANG FORMATION, EILA FIELD, NORTH SUMATRA BASIN - Novanis Punto Aji, Bondan
Eila Field is an offshore oil and gas field located in the North Sumatra Basin, North Sumatra Province, with approximately 25 km2. The study focuses on the SB2-FS3 interval in the Eila Field, which is part of Lower Keutapang Formation. This study objectives are to understand the geological settings, reservoir characterizations and estimate hydrocarbon reserves in SB2-FS3 interval. The data used in this study are well data which include core description summary, cuttings descriptions, wireline logs, DST data, and 2D seismic data. The data were analyzed through sequence stratigraphy analysis, facies and depositional environment analysis, petrophysical analysis, subsurface geological mapping, and hydrocarbon reserve estimation. Sequence stratigraphy analysis shows the study interval is in SB2-FS3 is LST/TST and HST deposits. The interval SB2-FS3 is divided into four reservoirs based on parasequence, namely: Reservoir A (SB2-MFS2), Reservoir B (MFS2-FS2), Reservoir C (FS2-SB3), and Reservoir D (SB3-FS3). The result of facies analysis, based on the description of core and cuttings at the SB2-FS3, interval shows four lithofacies are Smf, Sfvf, Swl, and Fsm, which are composing three facies associations, tidal channel, tidal flat, and tidal sand bar. These facies associations compose Tide-dominated Estuary as a depositional environment. Petrophysical analysis shows that the study interval has an average value of shale volume 0.08-0.26; effective porosity 0.19-0.26; water saturation 0.73-0.82. The cutoff value for shale volume is 0.47; effective porosity is 0.145; water saturation is 0.84. The seismic interpretation shows an anticline structure with northwest-southeast orientation that become the main hydrocarbon trap and cut by several normal faults with northeast-southwest orientation. The estimated hydrocarbon reserves for OGIP is 30.56 BSCF and OOIP is 1.19 MMSTB.